2020
DOI: 10.1186/s12917-020-02546-6
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis due to Erysipelothrix rhusiopathiae in a dog – a case report

Abstract: Background Infective endocarditis is a rare but severe condition associated with a high mortality rate in small animal patients. This condition is caused by a microbial (most often bacterial) infection of the valvular portion of the endocardium, from which proliferative and/or erosive lesions on the cardiac valves or immediately adjacent structures develop. The two most commonly affected cardiac valves are the aortic and mitral valves. Case presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…E. rhusiopathiae is a small, Gram-positive, slender, straight, rod-shaped bacterium that causes erysipelas in swine and many other animals [3][4][5][6][7][8]. Swine erysipelas can cause pyrexia, lameness, characteristic diamond skin lesions, and even sudden death in growing and adult swine [9]. It occurs worldwide, causing huge economic loss [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…E. rhusiopathiae is a small, Gram-positive, slender, straight, rod-shaped bacterium that causes erysipelas in swine and many other animals [3][4][5][6][7][8]. Swine erysipelas can cause pyrexia, lameness, characteristic diamond skin lesions, and even sudden death in growing and adult swine [9]. It occurs worldwide, causing huge economic loss [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Although vegetative valvular endocarditis has been described in association with Erysipelothrix spp. infection in humans and other animals (Gorby and Peacock, 1988;Cabrera-García et al, 2020), it was not observed in infected SSOs, possibly due to small sample size rather than differing pathogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…Erysipelothrix is commonly an occupation-related infection that can be associated with farm animals or marine life, 2 and it can also be found in domesticated animals such as dogs and pigs. 9 Transmission of E. rhusiopathiae has also been seen from insects who collect a blood meal from mice and birds. 10 Although the source of transmission could not be confirmed for our patient, it can be inferred from the history that the vector may have been an insect which caused an erythematous plaque.…”
Section: Discussionmentioning
confidence: 99%